2015
DOI: 10.1139/apnm-2014-0485
|View full text |Cite
|
Sign up to set email alerts
|

Piecing together the puzzle of perilipin proteins and skeletal muscle lipolysis

Abstract: The regulation of skeletal muscle lipolysis and fat oxidation is a complex process involving multiple proteins and enzymes. Emerging work indicates that skeletal muscle PLIN proteins likely play a role in the hydrolysis of triglycerides stored in lipid droplets and the passage of fatty acids to the mitochondria for oxidation. In adipocytes, PLIN1 regulates lipolysis by interacting with comparative gene identification-58 (CGI-58), an activator of adipose triglyceride lipase (ATGL). Upon lipolytic stimulation, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 99 publications
(226 reference statements)
2
33
0
Order By: Relevance
“…There was a down-regulation in nearly all of the genes responsible for the transport of FFAs into the muscle cells, and the synthesis of TGs from FFAs (53), including CD36, ACSL1, ACSL6, AGPAT9/glycerol-3-phosphate acyltransferase 3, glycerol-3-phosphate acyltransferase 1, mitochondrial, AGPAT1, AGPAT3, AGPAT6, lipin 1-3, and DGAT1-2. PLIN2, which coats lipid droplets and appears to be important for lipid droplet growth and stability (54), was also up-regulated after rotator cuff tear, whereas PLIN5, which also coats lipid droplets but also helps to target fatty acids to mitochondria for oxidation (54), was down-regulated. Consistent with these findings, genes involved with hydrolyzing TG stored in lipid droplets in fatty acids (53,55) were down-regulated after injury, including ATGL and PNPLA3, hormone-sensitive lipase, and monoglyceride lipase.…”
Section: Discussionmentioning
confidence: 99%
“…There was a down-regulation in nearly all of the genes responsible for the transport of FFAs into the muscle cells, and the synthesis of TGs from FFAs (53), including CD36, ACSL1, ACSL6, AGPAT9/glycerol-3-phosphate acyltransferase 3, glycerol-3-phosphate acyltransferase 1, mitochondrial, AGPAT1, AGPAT3, AGPAT6, lipin 1-3, and DGAT1-2. PLIN2, which coats lipid droplets and appears to be important for lipid droplet growth and stability (54), was also up-regulated after rotator cuff tear, whereas PLIN5, which also coats lipid droplets but also helps to target fatty acids to mitochondria for oxidation (54), was down-regulated. Consistent with these findings, genes involved with hydrolyzing TG stored in lipid droplets in fatty acids (53,55) were down-regulated after injury, including ATGL and PNPLA3, hormone-sensitive lipase, and monoglyceride lipase.…”
Section: Discussionmentioning
confidence: 99%
“…FFAs (48), including CD36, ACSL1, ACSL6, AGPAT9/GPAT3, GPAM, AGPAT1, AGPAT3, AGPAT6, lipin 1-3, and DGAT1-2. Perilipin 2, which coats lipid droplets and appears to be important for lipid droplet growth and stability (49) was also upregulated after rotator cuff tear, while perilipin 5 which also coats lipid droplets but also helps to target fatty acids to mitochondria for oxidation (49), was downregulated. Consistent with these findings, genes involved with hydrolyzing triglyceride stored in lipid droplets into fatty acids (48,50) were downregulated after injury, including ATGL and PNPLA3, hormone sensitive lipase, and monoglyceride lipase.…”
Section: Discussionmentioning
confidence: 99%
“…Each PLIN family member likely performs a unique function in the regulation of lipid droplet dynamics [35], and PLIN1 plays a "switch" role in regulating lipolysis. Native PLIN1 may serve as a barrier, protecting droplet triglycerides from basal lipolysis, whereas phosphorylated PLIN1 could indirectly activate ATGL [36,37]. Previous studies have found that the expression of PLIN1 was higher in muscles with high IMF contents [34,38].…”
Section: Ppar Pathway Regulates Weakened Lipolysis and Enhanced Lipogmentioning
confidence: 98%